The crystal structure of (E)-1-((3)-nitrophenyl)pyren-3-(pyren-1-yl)prop-2-en-1-one, C25H15NO3 - Barrientos Claudio; Squella J. Arturo; Moris Silvana (Zeitschrift für Kristallographie - New Crystal Structures)
C25H15NO3, triclinic, P1̄ (no. 2), a = 8.4899(3) Å, b = 10.1383(4) Å, c = 11.3806(5) Å, α = 78.373(1)°, β = 72.020(1)°, γ = 73.381(1)°, V = 885.89(6) Å3, Z = 2, Rgt(F) = 0.0439, wRref(F2) = 0.1290, T = 296.15 K.